Asymmetrical Local Elections: Affirmation of Sovereignty for People's Welfare - Tukina (Jurnal Bina Praja, 2020)
The purpose of this study is to find the background of the Direct of Regional Heads Election, their relationship with welfare and asymmetric regional elections. The study conduct with a qualitative descriptive method where the role of researchers is very important. Research continues  conducted until researchers feel enough to answer the research goal. Data obtained in the field and exposed by inductive analysis through planned stages. To support data retrieval research; participatory observation, looking for key informants, in-depth interviews, discussions and literature. Direct Election by people gives the role of the local community to choose leaders, check and balance the Government and as a form of direct accountability. Elections related to political and economic access, with that access there is a connection between the elections, people's sovereignty for welfare. Recommendation;  Regional Head Election needs  adapted to the characteristics of diverse communities and online society development. National-local Election Commission needs to think and do in new ways especially in the COVID 19 era to use Electronic Election (E-Voting). E-Voting is in line with the Internet-based Society and Technology development. Asymmetrical regional head elections need to answer that challenges.